Comprehensive risk assessment of leachate from unsanitary landfills in major cities of Bangladesh - Md. Tushar Ali; Quazi Hamidul Bari; Mst. Tahera Khatun (Alexandria Engineering Journal, 2025)
Unsanitary landfills in Bangladesh pose critical environmental risks due to inadequate leachate management, particularly in rapidly urbanizing cities. This study presents the first multi-city landfill leachate risk framework for low-resource settings, based on 20 integrated spatial datasets spanning climatic, geospatial, and infrastructural parameters. It introduces a novel approach by integrating hazard, exposure, and vulnerability analysis across eight major cities. The study employs a Data Envelopment Analysis (DEA) and Principal Component Analysis (PCA) to quantify risk and assess the efficiency of its components. Additionally, a Bootstrap approach is applied to refine DEA-derived values from limited sample data, enhancing accuracy and enabling comparisons of efficiency and confidence intervals. The study also establishes six geographic zones using spatial interpolation to systematically assess risks in the remaining 56 cities of the country. The results reveal that DEA 15–20 % underestimates efficiencies compared to the Bootstrap-DEA approach. Overall, Dhaka and Chittagong fall into the extreme risk category, Sylhet into very high, and Barisal into high, while other cities remain at low to very low-risk levels. The zoning analysis further highlights elevated risk in the central and eastern regions, whereas the northern and northwestern areas are in safer zones with minimal environmental risk. PCA showed that the first three components explained 79.1 % of the total variance, with PC1 accounting for 39.0 %. This study provides valuable insights for environmental engineers and policymakers on effective leachate management, emphasizing city-specific parameters, while also establishing a framework for global environmental risk assessments, particularly in sectors with limited datasets and resource-constrained countries.